(untitled) (Acta Scientiarum. Biological Sciences, 2020)
The crab Ucides cordatus is an important feature of mangroves in the North and Northeast of Brazil. In 2002 a large mortality was reported on this species in the Jaguaribe River Estuary. In order to investigate the possible causes specimens were collected monthly between May 2002 and December 2003 at five sites: Fortim (E1), Fortim (E2), Cumbe (E3) Aracati (E4) and Guajiru (E5). The mangrove structure and environmental parameters (salinity, pH, temperature and DO) were also evaluated. Water was collected for suspended solids analysis, BOD and nutrient levels. Salinity decreased in the rainy season, with no significant variation of pH and temperature. Dissolved oxygen levels had a mean of 5.7 mg L-1. Suspended solids increased at site E4, with BOD varying at E1 and E2 during the dry season. The same was observed at sites E1, E2 and E3 during the rainy season. Ammonia levels at E1 and E2 and phosphorus in all seasons, increased with rain events. Four lines of investigation were adopted: biometry, histology, hematology, and bioassay. There was no significant difference between animals in biometrics and histology showed no cellular alterations. However, hematology showed a significant difference between the E1 and E3 sites due to depletion in the number of hemocytes in E1, probably in response to environmental impacts. This can lead to poor immunity, leading to opportunistic pathogen infections such as viruses, bacteria and fungi. The bioassay showing no abnormal behavior or mortality. The structure the of mangrove was developed in all areas, except in E5 which served as a control site, with significant environmental stress with high levels of herbivorous growth (> 50%) and a salinity of around 50 ‰. It is believed that the mortality of the crabs was an occasional occurrence, probably due to toxin production by some fungal organism.